Brebes trade: A SOAR-driven approach to enhancing competitiveness and growth - Febrayanto, Catur Raharjo (Indonesia Auditing Research Journal, 2025)
The trade sector in Brebes Regency, Indonesia, exhibits a unique landscape with a strong focus on agriculture and local markets, presenting challenges in achieving significant growth. This study aims to analyze the trade sector in Brebes using the SOAR framework to identify key areas for development. The research methodology involved assessing the strengths, opportunities, aspirations, and potential results of the trade sector in Brebes. The analysis revealed that while wholesale and retail trade dominate the sector with a contribution of 85.63%, motor vehicle and motorcycle trade lag behind at 14.37%. Despite slow projected growth, strategic innovations in infrastructure, logistics, and competitiveness have the potential to drive significant expansion in the trade sector. By leveraging the county's agricultural base, strategic location, and emerging opportunities such as e-commerce and government support for MSMEs, Brebes can enhance its trade sector's competitiveness and economic contribution. The study underscores the importance of strategic planning and innovative initiatives to propel the trade sector in Brebes towards a more vibrant and prosperous future.